Healthcare professionals’ knowledge, attitudes and practices toward deprescribing: a protocol of cross-sectional study (Desmedica Study—Brazil) - Luciane Cruz Lopes; Fabiane Raquel Motter; Nathalia Margarida Cantuaria (BMJ Open)
Background Deprescribing is the planned and supervised process of dose reduction or stopping of medication that might be causing harm, or no longer be of benefit. It is an activity that should be a normal part of care/the prescribing cycle. Although now broadly recognised, there are still challenges in its effective implementation.Objectives To develop and validate an instrument to measure Brazilian healthcare professionals’ knowledge, attitudes and practices towards deprescribing.Methods This study will include the following steps: (1) development of the preliminary instrument; (2) content validation; (3) pilot study; (4) evaluation of psychometric characteristics. After the elaboration of items of the instrument through the literature review, we will use a hybrid Delphi method to develop and establish the content validity of the instrument. Further, a pilot survey will be performed with 30 healthcare professionals. Finally, for the evaluation of psychometric characteristics, a cross-sectional study will be accomplished with a representative sample of different healthcare professionals from different Brazilian states using respondent-driven sampling. Exploratory factor analysis and confirmatory factor analysis will be performed. For assessing the model fit, we will use the ratio of χ2 and df (χ2/df), comparative fit index, the goodness of fit index and root mean square error of approximation. In addition, the reliability of the instrument will be estimated by test–retest reproducibility and Cronbach’s alpha coefficient (α).Ethics and dissemination The Ethics Committee for Research at the University of Sorocaba (ethics approval number: 3.848.916) approved the study. Study findings will be circulated to healthcare professionals and scientists in the field through publication in peer-reviewed journals and conference presentations.